Altruistic normative interactions: strengthening organizational citizenship behavior and improving managerial effectiveness - Panca Tuah Tuha (Jurnal Mantik, 2023)
Normative altruistic interactions are interactions between people who are motivated to help each other because of a sense of moral obligation. This interaction is based on the belief that people should help others, even if they do not receive anything in return. The mediating role of normative altruistic interactions is tested to fill the gap between Organizational Citizenship Behavior and its influence on managerial effectiveness. Using descriptive quantitative methods and a sample of 202 respondents consisting of managers at coal mining companies. Data analysis was carried out using AMOS Structural Equation Modeling (SEM), and the Sobel test was carried out. The results obtained were carried out with a Z score of 3,800, more than 1.96, one-way and two-way probabilities of 0.000, ? 0.05. The chi-square value is 1, 270 with df 1 (42–21) where the probability of a test difference of 25.97% means higher than 5% indicating the model is full mediation. The role of altruistic normative interaction variables is important in bridging the influence of Organizational Citizenship Behavior on managerial effectiveness. This effect is stronger if the normative altruistic interaction is high. Individuals who have high norms of altruism and norms of compliance will be more likely to perform. High standards of altruism and conformity will make people more willing to engage in organizational citizenship behavior which will ultimately increase managerial effectiveness